(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Penal System of any nation shows the success and strength of controlling crimes and even showcases the consideration of humanity towards criminal. Both past and the future hold equal importance in the field of victimology. What is happening in the field of victimology in the future is as important as the knowledge about the history of this science and from whose shoulder we stem from. Great scholar Beccaria (1764) initiated a revolution in the criminal justice system and used the available means of scientific methods at the time to address the topic of abuse of power. He wrote a book and tried to tame the power of the state they harassed the offenders by inventing the concept of human rights. The offender came to be seen as a victim who had specific rights and this served as an armour against the mighty. The origins of victimology cab be traced to the 20th century, the founder of the discipline, Hans von Hentig, came from the Italian school of scupla positive. He gave birth to the idea of compensation and the state was responsible for the same. The word “compensation”—the state or the offender. During the time of Victorian law, the reform commission in 1922 mentions that “if the human rights of the offenders are sacred, then the human rights of the victims were no less sacred.” In 1949, Frederik Wertham used the word “victimology” and gained popularity due to his fight against “comics.” He laid emphasis on the ideas of mass victimization, financial profits by producers of poisonous gases, colonialism and racial discrimination.